2018
DOI: 10.1002/slct.201800728
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐[1H‐indol‐2‐yl(1H‐indol‐3‐yl)methyl]phenol and Its Application in Aqueous Rechargeable Lithium‐Ion Batteries

Abstract: The present work focuses on a novel synthetic approach for a bis‐Indole derivative and its applications in energy storage devices. Here, an aqueous rechargeable lithium ion battery (ARLIB) with organic active material electrodes of inexpensive and sustainable, bis‐indole derivative called 2‐[1H‐indol‐2‐yl(1H‐indol‐3‐yl)methyl]phenol (b‐IMP) and Lithiated quinizarin (Li‐QZ) are used as cathode and anode respectively in saturated Li2SO4supporting electrolyte. The electrochemical activities of these organic redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Emodin, a hydroxyl‐ and methyl‐functionalized species derived from plant extracts, allowed the construction of a cell with a stable voltage and a good initial capacity but showed a capacity loss of 70 % over 80 cycles . Using quinizarin (1,4‐dihydroxyanthraquinone) in combination with 2‐[1 H ‐indol‐2‐yl(1 H ‐indol‐3‐yl)methyl]phenol, a cell comprising two organic active materials (but still a Li + ‐based electrolyte) was built but revealed a voltage curve that featured no distinct plateaus . Takeda et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emodin, a hydroxyl‐ and methyl‐functionalized species derived from plant extracts, allowed the construction of a cell with a stable voltage and a good initial capacity but showed a capacity loss of 70 % over 80 cycles . Using quinizarin (1,4‐dihydroxyanthraquinone) in combination with 2‐[1 H ‐indol‐2‐yl(1 H ‐indol‐3‐yl)methyl]phenol, a cell comprising two organic active materials (but still a Li + ‐based electrolyte) was built but revealed a voltage curve that featured no distinct plateaus . Takeda et al.…”
Section: Methodsmentioning
confidence: 99%
“…[39] Using quinizarin (1,4-dihydroxyanthraquinone)i n combination with 2-[1H-indol-2-yl(1H-indol-3-yl)methyl]phenol, ac ell comprising two organic active materials (but still a Li + -based electrolyte) was built but revealed av oltage curve that featured no distinct plateaus. [40] Takeda et al demonstrated an anthraquinone derivative in which carbon atoms in the aromatic rings werer eplaced by nitrogen atoms. [41] Ar espective lithium-ion cell showedas loping voltage and an initial capacity of 250 mAh g À1 ,w hich decreased by 40 %w ithin 30 cycles.T he same contribution presented ac ell based on tetracyano-9,10-anthraquinonedimethane (TCAQ), which was already introduced in 2014 as ar edox-activeg roup in ap olymeric active material.…”
Section: Batterys Ystem Vmentioning
confidence: 99%
“…Owing to their importance in the biological field, the preparation of BIMs derivatives by various methods [13] has been studied well. However, their relevance in the materials field is quite limited, and only a few as selective anionic and chromogenic sensors, [14] and few electrochemical applications [15] are documented. The oxidation of the benzylic system [16] in BIMs can be achieved via DDQ [17] route, however, investigation of their photooxidation behavior has not been explored.…”
Section: Introductionmentioning
confidence: 99%